1995
DOI: 10.1159/000218633
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Trial of Dichloromethylene Bisphosphonate (Clodronate) in Patients with Multiple Myeloma Requiring Treatment. A Multicenter Study

Abstract: Background: Characteristic features of multiple myeloma are bone resorption, osteoporosis and osteolytic lesions. Bisphosphonates can inhibit osteoclast activity and bone resorption. In this controlled randomized multicenter trial the effect of the bisphosphonate clodronate on the progression of bone involvement in multiple myeloma was evaluated. Patients and Methods: 170 patients with multiple myeloma requiring treatment and with bone involvement were recruited and randomized. All patients received 15 mg/m Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Bisphosphonates have been evaluated in several large randomized trials in myeloma patients also receiving chemotherapy. Oral etidronate given daily showed no clinical benefit [2], whereas the use of oral clodronate daily produced variable clinical results in three randomized trials [11,16,17]. Oral administration of pamidronate was ineffective in reducing the skeletal complications of these patients [18].…”
Section: Opinion Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Bisphosphonates have been evaluated in several large randomized trials in myeloma patients also receiving chemotherapy. Oral etidronate given daily showed no clinical benefit [2], whereas the use of oral clodronate daily produced variable clinical results in three randomized trials [11,16,17]. Oral administration of pamidronate was ineffective in reducing the skeletal complications of these patients [18].…”
Section: Opinion Statementmentioning
confidence: 99%
“…• These agents have been evaluated alone and as adjunctive therapy to primary anti-cancer treatment in patients with cancers involving the bone, including multiple myeloma [2,[11][12][13][14][15][16][17][18][19][20]43]. Recent, large, placebocontrolled clinical trials have shown the efficacy of bisphosphonates in reducing skeletal complications in myeloma patients, suggesting that these agents may also alter the overall course of the disease.…”
Section: Bisphosphonates In Myeloma Bone Diseasementioning
confidence: 99%
“…The effectiveness of bisphosphonates has been evaluated by their ability to reduce skeletal events: (1) new bone lesions (x-rays or scintigraphy) ; (2) fractures (radiologic or clinical examination) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20); (3) bone pain (analgesics, visual analogue scale, pain score, requirement of irradiation or isotope therapy) (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41); (4) performance status (Karnofsky, Zubrod, ECOG) (11 -20, 31-41); (5) quality of life measures (16-20, 36, 37, 40, 41); (6) hypercalcemia (11 -21, 25, 31 -38); (7) measurements of different bone markers (11 -13, 20, 28, 30, 35 -38, 40 -44); and (8) survival (11 -13, 15, 18 -20, 34 -38, 40, 41). Study endpoints have been defined as a reduction of skeletal events and complications as well as an improvement of quality of life and pain relief.…”
Section: Assessment Of Skeletal E6entsmentioning
confidence: 99%
“…The same applies to myeloma patients. It is now clear that bisphosphonates combined with chemotherapy are superior to chemotherapy alone in multiple myeloma (32)(33)(34)(35)(36)(37)(38). The subgroup analysis of the Finnish myeloma study showed also that patients without any bone lesion at baseline had benefited from a bisphosphonate because only 2.6% on clodronate had developed skeletal lesions after 2 years in comparison with 11.1% on placebo (p =0.03) (35).…”
Section: Contro6ersiesmentioning
confidence: 99%
“…Side effects were similar in both groups. A second randomized trial using clodronate in patients receiving melphalan and prednisone showed a reduction of pain and analgesic consumption under bisphosphonate treatment [26]. In a trial by the British MRC group [27], 536 patients with recently diagnosed multiple myeloma were randomized to receive in addition to chemotherapy either clodronate 1,600 mg daily or a placebo.…”
Section: Trials In Patients With Osteolytic Lesionsmentioning
confidence: 99%